(untitled) (Swiss Medical Weekly, 2025)
BACKGROUND: Physician wellbeing has a direct impact on patient care. Meta-analyses have concluded that interventions are moderately effective at reducing physician burnout, but new studies are needed to target populations at higher risk (e.g. young physicians) and determine which interventions might be most effective. METHOD: Using matched questionnaires, we conducted a cross-sectional pre-post study of a multimodal intervention to promote physician wellbeing. The intervention involved a change in institutional culture, information on occupational wellbeing, and the organisation of undisturbed lunch breaks and short breaks during the day. The primary outcome was the proportion of physicians satisfied with their job (scoring >3 points on the Work-Related Quality of Life [WRQoL] scale). Secondary outcomes were overall WRQoL score, WRQoL subscale scores, number of short breaks taken during the working day, number of lunch breaks taken, physicians’ likeliness of recommending their job to peers, monthly overtime hours worked and monthly sick days. Subgroup analyses included women vs men, residents vs chief residents/senior physicians, and participants with vs without children. We also explored potential factors influencing WRQoL in the pre-intervention population. RESULTS: Pre- and post-intervention questionnaires were returned by 134 (63%) and 87 (42%) physicians, respectively, with 75 responding to both (matched). The intervention significantly increased the proportion of physicians satisfied with their job (from 49/75 [65%] to 58/75 [77%], p = 0.02), median overall WRQoL score (from 3.3 [IQR: 2.8–3.8] to 3.5 [IQR: 3.1–3.8], p <0.01), median Home-Work Interface subscale score (from 2.7 [IQR: 2.0–3.3] to 3.0 [IQR: 2.3–3.7], p = 0.01) and median General Well-Being subscale score (from 3.4 [IQR: 2.6–4.0] to 3.6 [IQR: 3.0–4.0], p <0.01). Residents showed a greater increase in overall WRQoL median score (from 3.2 [IQR: 2.7–3.6] to 3.5 [IQR: 3.3–3.8]) than chief residents/senior physicians (3.3 [IQR: 2.9–3.9] to 3.4 [IQR: 3.0–3.8], p <0.01 for group difference). No significant differences were seen in other subgroups or secondary outcomes in the matched population. Among the 134 participants in the pre-intervention period, those taking a daily lunch break, sleeping 7 hours or more or self-reporting doing sports activities on weekdays had higher overall WRQoL scores. CONCLUSIONS: This wellbeing intervention increased physicians’ WRQoL scores. However, the difference was small and its relevance remains uncertain.